Anomalous electron-electron interactions in epitaxial graphene on SiC. (30th October 2021) - Yang, Y.; Gao, K.H.; Wang, W.J.; Yu, G.; Sun, Y.; Zhang, X.H.; Li, Z.Q.
Abstract: Electron-electron interactions (EEI) play a pivotal role in the transport behavior of carriers confined in a two-dimensional system. The strength of the interaction can be tuned by changing carrier concentration in a conventional two-dimensional system, while it expectedly cannot be controlled in monolayer graphene with a linear dispersion relation since the interaction parameter is not related to carrier concentration. Here, an anomalous carrier-concentration dependence of the EEI is observed in epitaxial graphene on SiC. From quantum transport measurement, a logarithmic temperature dependence of the Hall coefficient is obtained, which is a manifestation of the EEI. From the logarithmic temperature dependence, the EEI-related factor K e e is extracted. Unexpectedly, the extracted K e e shows an increase on increasing carrier concentration, which is further confirmed by analyzing logarithmic correction to the Drude conductivity. This can be attributed to the carrier-concentration dependence of Fermi-liquid constant F 0 σ due to gas absorption, which offers a route to control the EEI in graphene. Graphical abstract: Image 1